The development of an academic dishonesty attitude inventory for college students - Entao, Elisa Bernadette P. (Animo Repository, 1999)
This study develops an instrument entitled Academic Dishonesty Attitude Inventory (ADAI) which intends to measure attitude towards academic dishonesty among college students. Statements included in the initial item pool were based on a survey conducted among 89 male and 97 female college students and on various related studies. Eight item judges whose fields of expertise are in psychology and guidance and counseling, test and measurement, and education reviewed the initial item pool. These item judges were tasked to determine the appropriateness of the items with constructs found under academic dishonesty. A pilot test was conducted to check whether the items were clear and understandable to the respondents. The field test was given to a sample of 500 (250 males and 250 females) college students from two private schools in Manila. Item analysis and factor analysis were applied to the data gathered from the field-testing. Results from the factor analysis confirmed the presence of five forms of academic dishonesty: I-Cheating, II-Plagiarism, III-Dishonest Conduct, IV-Falsification, and V-Collusion. The reliability of the instrument was established by computing for the Cronbach Alpha Reliability Coefficient for each factor. Moreover, the reliability of coefficient per factor was as follow: I - .9535039, II - .9007009, III - .8667738, IV - .9333008, and V - .8596468. The instrument was trimmed down to 84 items in its final form. Separate norms were constructed for each factor for a more specific evaluation of attitudes. Likewise, an over all norm was also created for a more holistic interpretation of the test results. The interpretations of scores were mainly based on percentile ranks. The outcome of the study revealed that the factors namely cheating, plagiarism and falsification were mostly reflected in the form of behavior, beliefs and feelings. However, the factor known as dishonest conduct was mostly manifested in overt behavior, while collusion was measurable through the form of beliefs and the affective states. The study proved that the Academic Dishonesty Attitude Inventory was a valid and reliable instrument for measuring attitudes towards academic dishonesty. Finally, the findings of the study suggested that further validity and reliability measures be conducted for the improvement of the instrument.